Data Logging Implementation on Web-Based Communication on Arduino Devices - Tsani, Yasyfi Rahmanda; Subardono, Alif (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Arduino is one of the microcontroller devices commonly used on the Internet of Things. This research designed and objectified web-based data logging system that aimed to record communication and sensir data in iot devices, so it could monitor log data in iot. Devices from this data logging system was created using arduino uno r3 with adding ethernet shield modul and temperature sensor DHT 11. in iot devices, there is an important parameter, that is date time as a history in data logging sistem using an actual time. Website was functioned as system for showing data from log data and could be monitored realtime. This system could record communication brtween arduino device and NTP server using internet network. Beside that?this system could record important parameters in the system such as IP source address, ip destination address, ip address in each node, device time, and room temperature information. Parameters that had been recorded would be stored to database, then would be showed in web data logging.